2020
DOI: 10.1126/scisignal.aba5754
|View full text |Cite
|
Sign up to set email alerts
|

Daily alcohol intake triggers aberrant synaptic pruning leading to synapse loss and anxiety-like behavior

Abstract: Alcohol abuse adversely affects the lives of millions of people worldwide. Deficits in synaptic transmission and in microglial function are commonly found in human alcohol abusers and in animal models of alcohol intoxication. Here, we found that a protocol simulating chronic binge drinking in male mice resulted in aberrant synaptic pruning and substantial loss of excitatory synapses in the prefrontal cortex, which resulted in increased anxiety-like behavior. Mechanistically, alcohol intake increased the engulf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 88 publications
2
39
0
Order By: Relevance
“…Therefore, a better understanding of the microglia reactivity and associated brain immune-pathways in response to psychostimulants is paramount to implement relevant interventions for treating addictive behaviors. In accordance, we have recently demonstrated that binge alcohol administration to adult mice causes aberrant synaptic pruning and loss of prefrontal cortex excitatory synapses, increasing anxiety-like behavior, which is prevented by pharmacological blockade of Src activation or by reducing TNF production in microglia 21 .…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Therefore, a better understanding of the microglia reactivity and associated brain immune-pathways in response to psychostimulants is paramount to implement relevant interventions for treating addictive behaviors. In accordance, we have recently demonstrated that binge alcohol administration to adult mice causes aberrant synaptic pruning and loss of prefrontal cortex excitatory synapses, increasing anxiety-like behavior, which is prevented by pharmacological blockade of Src activation or by reducing TNF production in microglia 21 .…”
Section: Introductionsupporting
confidence: 59%
“…TNF knockout mice in the C57BL/6 background (referred herein as TNF KO) were kindly supplied by Professor Rui Appelberg (University of Porto). TNF KO mice 21 were maintained at i3S and genotyped by PCR using ATCCGCGACGTGGAACTGGCAGAA (forward) and CTGCCCGGACTCCGCAAAGTCTAA (reverse) primer pair. IP3R2 KO mice 23, 24 were held at ICVS animal facility and genotyped PCR using the primer pairs: WT (F, 5’-ACCCTGATGAGGGAAGGTCT-3’; R, 5’-ATCGATTCATAGGGCACACC-3’) and mutant allele (neo-specific primer: F, 5’-AATGGGCTGACCGCTTCCTCGT-3’; R, 5’-TCTGAGAGTGCCTGGCTTTT-3’).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the small fraction of microglia in bulk brain tissue, it is difficult to study the expression of this transcription factor in transcriptomic datasets from whole brains. Some studies using animal models have reported that chronic alcohol consumption can influence the expression of PU.1 in isolated microglia 35 and peripheral lung macrophages 36,37 . However, these studies report the consequences of drinking on PU.1 expression whereas our study uses genomic evidence to demonstrate that regulation of innate immune response likely underlies, at least in part, susceptibility to increased drinking and eventual risk for AUD.…”
Section: Discussionmentioning
confidence: 99%
“…The following markers were used to characterize microglia in the samples: CD45 CD11b and Ly6C. Microglia were collected from the brains of control and mutant mice using density gradient separation as before (4,37). Single-cell suspensions (5 x 10 5 cells) were incubated with different mixes of FACS antibodies for 30 min at 4°C in the dark.…”
Section: Flow Cytometry and Cell Sortingmentioning
confidence: 99%